2017
DOI: 10.5788/27-1-1397
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary Tradition vs. Pictorial Corpora: Which Vocabulary Thematic Fields Should Be Illustrated?

Abstract: Abstract:The latest research conducted by De Jong (2014) indicated that only a few European academic dictionaries, among over one hundred and fifty, use pictorial illustrations. On the other hand, it has been mentioned several times in the literature (related to both printed and electronic reference works) that visual content makes a general dictionary more attractive for the user. Therefore a new methodology, enhancing graphical strategy in lexicography, would be proposed. Firstly, a thematic division of mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition, the developed dictionary also contains images that provide visuals to students. The results of the previous research found that children will be more interested in reading if the reading material contains visual elements (Biesaga, 2017). This is also identified by those who find that students' reading interest will be higher if they are given a concrete concept and it is in accordance with their learning method (Ratminingsih & Budasi, 2018;Sibanda, 2019).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the developed dictionary also contains images that provide visuals to students. The results of the previous research found that children will be more interested in reading if the reading material contains visual elements (Biesaga, 2017). This is also identified by those who find that students' reading interest will be higher if they are given a concrete concept and it is in accordance with their learning method (Ratminingsih & Budasi, 2018;Sibanda, 2019).…”
Section: Resultsmentioning
confidence: 87%
“…Multilingual dictionary is a dictionary which provides a list of words of more than two languages (Bask & Mumcu, 2018;Yurtbaģı, 2017). Thematic dictionary is a dictionary which consists of simple words that come from a certain theme and sometimes followed by graphic or illustration (Biesaga, 2017). Meanwhile, picture or visual dictionary is a dictionary which adds pictures to visualize the meaning of words and mostly provides nouns (Smith & Davis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is because children in primary schools have different characteristics from adult learners. Children in primary schools prefer to learn using interactive media such as video, game, songs and physical activities such as singing and dancing (Biesaga, 2017;Pratama & Permana, 2018;Smith, Sanchez, Betty, & Davis, 2016;Ulfa, Salim, & Permana, 2017;Vitasmoro, Chandra, & Jatmiko, 2019).…”
Section: Introductionmentioning
confidence: 99%